2003
DOI: 10.1042/bj20031057
|View full text |Cite
|
Sign up to set email alerts
|

Mutational epitope analysis of Pru av 1 and Api g 1, the major allergens of cherry (Prunus avium) and celery (Apium graveolens): correlating IgE reactivity with three-dimensional structure

Abstract: Birch pollinosis is often accompanied by adverse reactions to food due to pollen-allergen specific IgE cross-reacting with homologous food allergens. The tertiary structure of Pru av 1, the major cherry (Prunus avium) allergen, for example, is nearly identical with Bet v 1, the major birch (Betula verrucosa) pollen allergen. In order to define cross-reactive IgE epitopes, we generated and analysed mutants of Pru av 1 and Api g 1.0101, the major celery (Apium graveolens) allergen, by immunoblotting, EAST (enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(114 citation statements)
references
References 34 publications
3
109
1
1
Order By: Relevance
“…[10], [120], [121], [122] and [123] [124], [125], [126], [127], [128], [129] and [130] However, other studies at different shifting offsets, with different peptides sizes, or both revealed different sets of immunodominant sequential epitopes for the same allergens. [29], [124], [125], [126], [127], [130] and [131] Nevertheless, approaches to use these alleged immunodominant peptides for the risk assessment of life-threatening symptoms, as well as the prediction of persistence in food hypersensitivity, were apparently successful.…”
Section: Diagnosis Of Food Allergy With Synthetic Sequential Epitopesmentioning
confidence: 99%
“…[10], [120], [121], [122] and [123] [124], [125], [126], [127], [128], [129] and [130] However, other studies at different shifting offsets, with different peptides sizes, or both revealed different sets of immunodominant sequential epitopes for the same allergens. [29], [124], [125], [126], [127], [130] and [131] Nevertheless, approaches to use these alleged immunodominant peptides for the risk assessment of life-threatening symptoms, as well as the prediction of persistence in food hypersensitivity, were apparently successful.…”
Section: Diagnosis Of Food Allergy With Synthetic Sequential Epitopesmentioning
confidence: 99%
“…Such substitutions may markedly affect the protein outer surface or directly involve contact residues important for the antigen-antibody interaction, thus reducing or abolishing antibody reactivity. The work presented in this issue of the Biochemical Journal by Neudecker and co-workers [6] clearly shows that the introduction of a proline residue at position 112 of Pru av 1, the major allergen of cherry, results in the disruption of the native tertiary structure of the molecule and thus an almost complete loss of IgE reactivity. Since the whole surface of a molecule is antigenic during a polyclonal response resulting from natural exposure [7], the single point mutation Ser 112 → Pro disrupting the native tertiary structure of Pru av 1 has a dramatic effect on the allergenicity of the whole protein.…”
Section: B-cell Epitopes and Cross-reactivitymentioning
confidence: 97%
“…We will only reach this goal if we are able to produce vaccines able to elicit strong protective immune responses independent of the patient-specific IgEbinding characteristics. As demonstrated by Neudecker et al [6], in the single case of an allergen from the pathogenesisrelated proteins, hypo-allergenic variants can be more easily and cost-efficiently produced by irreversibly preventing the folding process of an allergen, than by time-consuming mutation of residues that are assumed to be involved in the formation of IgE-binding epitopes. Such unfolded proteins, easily produced by single mutations introduced based on structural considerations, will retain almost, if not all, T-cell epitopes needed to provide B-cells with the necessary help to mount protective responses against allergens, and there is no reason to assume that this simple and efficient approach should not work in clinical practice.…”
Section: Ige Binding Allergy Vaccines and New Forms Of Immunotherapymentioning
confidence: 99%
“…The tertiary structure of Bet v 1 contains three surface patches that have conserved-amino acid sequences and structures with proteins from a variety of food including cherry, apple, hazelnut, peach, carrot, celery, and soya (Vieths et al, 2002). Among them conserved-IgE cross reactive region is the P-loop located between b-strands 2 and 3 of Bet v 1 and its homologs (Mirza et al, 2000;Neudecker et al, 2003). Elicitation of clinical allergy symptoms appears to be dependent on IgE binding to these structures, which is in direct contrast to that observed for other food allergens with linear IgE binding epitopes such as plant allergens from peanut (Ara h 1, Ara h 2, Ara h 3), soya (G2 Glycinin, P34/Gly m Bd 30K), wheat (ω-5 Gliadin), pollen (Jun a 1, Par j 1, Par j 2), nuts (Jug r 1, Ana o 1), and animal allergens from egg (Ovalbumin, Ovomucoid), shrimp (Tropomyosin), and milk (αs2-Casein) (Bannon & Ogawa, 2006).…”
Section: Discussionmentioning
confidence: 99%